Challenges for the Eurasian Economic Union Stock Markets: Analytical Approach - I. Z. Yarygina (Финансы: теория и практика, 2018)
Strengthening cooperation of the Eurasian Economic Union member-countries is the best solution to mitigate trade wars, unfair competition and worsening of international economic relations. The article reveals the significant correlation of the stock indices based on the analysis of the Eurasian Economic Union (EAEU) stock markets. The objective of the article is to introduce recommendations aimed at optimising cooperation of EAEU member-states and expanding their interaction in the financial sphere. Bloomberg data for 2000-2017 together with Excel tools have been used which allowed to prove the hypothesis of interdependence between the most developed stock markets: Moscow and Kazakhstan. The graphical analysis of the research has showed that a correlation between the indicators of these stock trading floors appeared in 2008, when the effects of the global financial and economic crisis were being overcome. There was no interdependence between the indices of the Moscow and Kazakhstan marketplaces until 2007. The research has showed that the EAEU stock market indices depend significantly on the production of raw materials and commodity prices. In the conditions of the financial relations development, the EAEU has proposed to use the world experience of strengthening the economic cooperation of European countries and their methods to overcome the crisis phenomena of the 1950s. The EAEU has to harmonize financial policies and financial relations, simplify entrepreneur access to lending, improve tax breaks for exporters of manufactured goods and grant subsidies to new sectors of the economy. The European experience can help the EAEU to overcome difficulties and solve cooperation problems.